HUBUNGAN KEWENANGAN PRESIDEN DENGAN DPR DALAM PEMBENTUKAN UNDANG-UNDANG PASCA PERUBAHAN UUD 1945 - RADJIJO - (Wacana Hukum, 2010)
Abstract:The amandemen of Indonesia constitution of UUD 1945 is resulting the movement of the power from Executive Heavy to Legislative Heavy.  This movement of lawmaking has the consequences on the law construction format which is currently under the President’s consideration whereas actually should be under the parliament’s consideration. Keywords: authority relationship, Executive Heavy, Legislative Heavy